Studies of anxiety and educational achievement - Frost, Barry P. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
There is conflicting evidence as to the nature of the relation between anxiety and educational achievement in children but the consensus seems to indicate a negative relation.